Wide-temperature-range perfect superelasticity and giant elastocaloric effect in a high entropy alloy. Issue 12 (2nd December 2019) - Li, Shaohui; Cong, Daoyong; Sun, Xiaoming; Zhang, Yong; Chen, Zhen; Nie, Zhihua; Li, Runguang; Li, Fuqiang; Ren, Yang; Wang, Yandong
ABSTRACT: The high entropy alloy concept offers unique opportunities for the design of advanced materials with unprecedented properties. However, hitherto most of the research efforts are focused on structural materials. Here, by employing the core effect of severe lattice distortion in high entropy alloys, a novel functional NiCuTiHf0.6 Zr0.4 high entropy alloy exhibiting intriguing wide-temperature-range perfect superelasticity in a broad temperature range from 263 to 463 K and giant elastocaloric effect with the maximum adiabatic temperature change of 9.3 K is developed. This work opens the door for designing high-performance superelastic and elastocaloric functional materials with the high entropy alloy concept. GRAPHICAL ABSTRACT: IMPACT STATEMENT: A novel functional high entropy alloy with intriguing wide-temperature-range perfect superelasticity and giant elastocaloric effect is sucessfully developed by employing the severe lattice distortion which leads to high yield strength.